PARENTING IS A FORM OF CHILDREN'S MORAL - Widya Masitah (Proceeding International Seminar of Islamic Studies, 2021)
The moral development of children has recently become an interesting issue to be the center of research attention. Many aspects become variables that can affect children's moral development, one of which is parenting. To analyze the relationship between parenting and children's moral, which was carried out by analyzing the items in the parenting style questionnaire and the children's moral development questionnaire, a study was conducted by taking a sample of 308 parents who had children aged 4-10 years in Patumbak District. Data were collected using the Google-form platform with a questionnaire designed and tested for validity. The collected data were then analyzed using the Contigency coefficient. The results showed that there was a relationship between the variable items of parenting and moral development in children.Keywords: Parenting, Children, Moral